Análise da sensibilidade do biodiesel B5 em frotas de transporte coletivo com motorização diesel - Oliveira Filho, Manoel Fernandes de (2011)
The aim of this study was investigate the consolidation of the biodiesel fuel used in (a) engines of urban and intercity bus companies, (b) a stationary engine. It was necessary to investigate and analyze, technologically, if the biodiesel fuels were presenting troubleshooting relative to wear of parts lied to fuel and to evaluate the consumption fluctuations of this fuel. The urban and intercity bus companies, localized in Natal, Rio Grande do Norte state, Brazil, had 41 and 12 vehicles, respectively. It were analyzed datasheet of each one vehicle during three years, since 2008 until 2010 and were interviewed the management of the maintenance team of bus companies relative to aspects concerning the substitution of the diesel fuel by the B5 biodiesel. The second aim of this study was visually inspect the wear of the parts directly lied to combustion process. For this reason, it was investigated a stationary engine, manufactured by Branco BD5, 5 HP of power, fueled by (a) diesel, (b) biodiesel B5, (c) biodiesel B20 and (d) diesel or biodiesel, both contaminated by distilled water. In this engine, its power utilizing biodiesel B5 versus diesel was lower about 5.2% and, in the investigated case of B20 versus diesel, it was lower around 11.5%